Effect of locoregional surgery in primary tumors on overall survival in patients with de novo stage IV breast cancer: a systematic review and meta-analysis - Sun, Yanbo; Ma, Hao; Li, Yingjie; Zhou, Can (Frontiers in Oncology, 2025)
BackgroundDue to the controversy in the therapeutic effect of locoregional surgery in primary tumors for patients with de novo stage IV breast cancer, the aim of this study was to evaluate the effect of locoregional surgery on overall survival in patients with de novo stage IV breast cancer.MethodsA computer-based search of PUBMED, Embase, and American Society of Oncology (ASCO) annual meetings abstracts was conducted to identify the prospective trials of the combination of locoregional surgery in primary tumors and systemic therapy in comparison with standard systemic therapy alone for patients with de novo stage IV breast cancer. Hazard ratios (HR) and 95% confidence intervals (CI) were calculated by universal inverse variance and combined across articles. Random-effects model and subgroup analyses were performed to ascertain the origin of this heterogeneity.ResultsA total of 2029 patients from 8 studies were included, with 1014 patients (49.98%) underwent locoregional surgery in primary tumors (surgery group) and 1015 ones (50.02%) with standard systemic therapy alone (no surgery group). Compared to patients in the no surgery group, participants with ER/PR positive breast cancer in the surgery group had improved overall survival (OS) (HR=0.77, 95%CI 0.55-0.93, P=0.01), and improved locoregional progression-free survival (HR=0.36, 95%CI 0.14-0.95, P=0.04) for all participants in the surgery group. And patients with bone-only metastases in the surgery group had insignificantly favorable OS than those in no surgery group (HR=0.70, 95%CI, 0.47-1.04, P=0.08).ConclusionOur study demonstrated that locoregional surgery in primary tumors was associated with improved OS for participants with ER/PR positive de novo stage IV breast cancer, and locoregional surgery in primary tumors could be worthy of clinical recommendation for patients with ER/PR positive de novo stage IV breast cancer.